2011
DOI: 10.1128/mcb.01141-10
|View full text |Cite
|
Sign up to set email alerts
|

R2D2 Organizes Small Regulatory RNA Pathways in Drosophila∇†

Abstract: Drosophila microRNAs (miRNAs) and small interfering RNAs (siRNAs) are generally produced by different Dicer enzymes (Dcr-1 and Dcr-2) and sorted to functionally distinct Argonaute effectors (AGO1 and AGO2). However, there is cross talk between these pathways, as highlighted by the recognition that Drosophila miRNA* strands (the partner strands of mature miRNAs) are generated by Dcr-1 but are preferentially sorted to AGO2. Here, we show that a component of the siRNA loading complex, R2D2, is essential both to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 66 publications
(162 reference statements)
6
66
0
1
Order By: Relevance
“…Importantly, miRNAs generated by dDcr1 cleavage are selectively loaded into Drosophila Ago1, while siRNAs generated by dDcr2 cleavage are selectively loaded into Ago2. This latter process is facilitated by a dsRNA-binding protein called R2D2 (Marques et al 2010;Okamura et al 2011;Nishida et al 2013). In contrast, in mammalian cells, miRNAs generated by hDcr are loaded equivalently well into all four Ago proteins (Wang et al 2012).…”
Section: Synthetic Microrna Duplexes Efficiently Program Risc In Dicementioning
confidence: 99%
“…Importantly, miRNAs generated by dDcr1 cleavage are selectively loaded into Drosophila Ago1, while siRNAs generated by dDcr2 cleavage are selectively loaded into Ago2. This latter process is facilitated by a dsRNA-binding protein called R2D2 (Marques et al 2010;Okamura et al 2011;Nishida et al 2013). In contrast, in mammalian cells, miRNAs generated by hDcr are loaded equivalently well into all four Ago proteins (Wang et al 2012).…”
Section: Synthetic Microrna Duplexes Efficiently Program Risc In Dicementioning
confidence: 99%
“…However, as the endo-siRNA population is extremely diverse, individual siRNAs are often not well-expressed (thus potentially challenging approaches to assay their depletion in dcr-2 mutants), and immunoprecipitation techniques do not necessarily distinguish intrinsically and peripherally bound species (thus potentially challenging the assessment of all reads in AGO2-IP libraries as bona fide siRNAs). As an alternative strategy, we previously showed that bulk endo-siRNAs are resorted to AGO1 complexes in mutants of the siRNA loading factor R2D2 or the siRNA effector AGO2 (Okamura et al 2011). Such resorting patterns, in which AGO1-IP small RNA reads exhibit relative abundance of r2d2 or ago2 ≫ wild-type .…”
Section: Drosophila Rdna Generates Sirnasmentioning
confidence: 99%
“…First, the proportions of resorted known siRNAs (from transposons and hairpin RNAs) in the AGO1 complexes substantially varied in the four AGO1-IP libraries (from 0.3% in dcr-2 mutant to 25.1% in r2d2 mutant, Supplemental Table S1, Sheet 2). Second, our previous Northern blotting analysis suggested that the levels of abundant miRNA species were not changed in these mutants (Okamura et al 2011). According to this normalization scheme, transposon-derived siRNAs were 27.3 and 36.5 times more abundant in the AGO1-IP libraries from r2d2 and ago2 mutant ovaries, respectively, than the AGO1-IP libraries from wild-type (Supplemental Table S1, Sheet 2).…”
Section: Drosophila Rdna Generates Sirnasmentioning
confidence: 99%
“…Although it might be questioned whether such atypically short species are functional, even 19-20-nt miR-317 isomiRs were relatively abundant in AGO1-IP data from ovaries and S2 cells, indicating that they populate endogenous miRISC complexes. Otherwise, AGO1-IP complexes normally select for more conventional ''miRNA-sized'' species (Czech et al 2008;Ghildiyal et al 2010;Okamura et al 2011).…”
Section: Trimming Of 39 Nucleotides From ''Long'' Mirtron Duplexesmentioning
confidence: 99%